Pengaruh Stabilitas Laba dan Stabilitas Arus Kas Operasional terhadap Nilai Perusahaan - Moh. Arrijal ‘Ilman Nafi’; Chairil Anwar; Dian Fahriani; Erlyna Tri Rohmiatun (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the influence of earnings stability and operating cash flow stability on firm value among IDX30 companies listed on the Indonesia Stock Exchange during the 2022–2025 period. A quantitative approach was employed using secondary data obtained from the companies' annual financial reports. The sample consisted of 21 companies selected via purposive sampling, resulting in 84 firm-year observations. Data analysis was conducted using multiple linear regression with the aid of SPSS version 27. The results indicate that earnings stability has a significant effect on firm value, with a regression coefficient of -0.103, a calculated t-value of -2.034, and a significance level of 0.046 (<0.05). Conversely, operating cash flow stability does not significantly affect firm value, showing a regression coefficient of 0.024, a calculated t-value of 0.586, and a significance level of 0.560 (>0.05). Simultaneous testing yielded a calculated F-value of 2.069 with a significance level of 0.135 (>0.05), indicating that earnings stability and operating cash flow stability, when combined, do not have a significant effect on firm value. These findings suggest that investors in IDX30 companies prioritize earnings consistency—viewing it as a signal of corporate performance quality—over operating cash flow stability when determining firm value. This study contributes theoretically by extending empirical evidence on the application of Signaling Theory in explaining the relationship between earnings stability, operating cash flow stability, and firm value. Methodologically, this study employs the coefficient of variation to measure earnings stability and operating cash flow stability in IDX30 companies. Practically, the findings provide useful insights for corporate management and investors in evaluating financial performance consistency as an important determinant of firm value.